Femtosecond infrared intrastromal ablation and backscattering-mode adaptive-optics multiphoton microscopy in chicken corneas - Gualda, Emilio J. (Optical Society of America, 2011)
The performance of femtosecond (fs) laser intrastromal ablation was evaluated with backscattering-mode adaptive-optics multiphoton microscopy in ex vivo chicken corneas. The pulse energy of the fs source used for ablation was set to generate two different ablation patterns within the corneal stroma at a certain depth. Intrastromal patterns were imaged with a custom adaptive-optics multiphoton microscope to determine the accuracy of the procedure and verify the outcomes. This study demonstrates the potential of using fs pulses as surgical and monitoring techniques to systematically investigate intratissue ablation. Further refinement of the experimental system by combining both functions into a single fs laser system would be the basis to establish new techniques capable of monitoring corneal surgery without labeling in real-time. Since the backscattering configuration has also been optimized, future in vivo implementations would also be of interest in clinical environments involving corneal ablation procedures.